Effectiveness of Distraction Techniques (Watching Animated Cartoons) in Reducing Pain During Infusion Insertion in Children at Multazam Hospital - Meiske A. Abas; Harismayanti; Rini Asnawati (Universitas Muhammadiyah Palu, 2026)
Infusion insertion is an invasive procedure that involves the insertion of the device into the body and is often performed on children during hospital treatment. This action can cause pain, worry, and less adaptive behavioral reactions in children. Therefore, non-pharmacological pain management efforts are needed that are easy to implement, one of which is through distraction techniques by watching animated cartoons. The problem in this study is the high level of pain experienced by children during IV installation. This study aims to determine the effect of distraction techniques of watching animated cartoons on the reduction of children's pain levels during IV installation. This study uses a quantitative method with a quasi-experimental design of a nonequivalent control group. The subjects of the study were preschoolers who underwent infusion and were divided into two groups, namely the intervention group and the control group. Pain level measurements were performed before and after the intervention using the Wong-Baker Faces Pain Rating Scale. The results of the univariate analysis showed that before the intervention, most of the children in both groups experienced moderate to severe pain. After the intervention, the group given the distraction of watching animated cartoons experienced a decrease in pain levels, characterized by increased mild pain and no severe pain found. Meanwhile, the control group still showed moderate to severe pain. The results of the Paired Sample t-Test showed a significant reduction in pain in the intervention group p. value (0.000 < 0.05), while in the control group there was no significant difference in p. value (0.336 > 0.05). The Independent Sample t-Test also showed a significant difference in pain reduction between the two groups of p. value (0.000 < 0.05). Conclusions: The distraction technique of watching animated cartoons has been shown to be effective in reducing children's pain during IV insertion and is recommended as a nonpharmacological intervention in pediatric care.